Spontaneous disseminated hydatidosis with uterine involvement in an 8-year-old child: a multidisciplinary approach - Mehdi Forooghi; Ali Tadayon; Shayan Yousufzai; Hossein Hosseini; Razie Vahdani; Rojan Abdollahzade Mirali; Simin Sharifi (BMC Infectious Diseases)
Abstract Background Spontaneous disseminated hydatidosis is a rare manifestation of Echinococcus tapeworm infection, especially in pediatric patients. This case report presents an unusual instance of multi-organ involvement in an 8-year-old Afghan girl living in Iran, a hydatid disease endemic region. Case presentation The patient presented with progressive abdominal distension, intermittent pain, nausea, and vomiting. Imaging revealed multiple hydatid cysts in the liver, peritoneal cavity, and uterus, suggesting disseminated disease without prior history of hydatidosis or exposure to definitive hosts. A multidisciplinary team performed an exploratory laparotomy, removing cysts from the liver, spleen, and uterus. Post-operative care included 12 months of Albendazole therapy to promote cyst shrinkage and reduce recurrence risk, with successful outcomes observed on follow-up. Conclusion This case highlights the importance of recognizing hydatid disease in endemic regions and the role of imaging and surgery in achieving good outcomes. This case also underscores the need for further research to elucidate the mechanisms behind such atypical presentations.